(untitled) (Nepalese Journal of Development and Rural Studies, 2019)
This study seeks to build a better understanding of the poverty alleviation progress in Nepal and to provide an affordable set of strategic options to the government of Nepal for reducing poverty. Despite significant improvements in economic and social indicators over the past four decades, the study shows that poverty is still widespread in Nepal. The study shows that there is significant progress in poverty alleviation in Nepal. The study indicates that poverty incidence has increased over the past 3 decades in Nepal, a period in which Nepal received substantial development assistance. Poverty is the main factor of declining the quality of living standard of Nepalese people. The objective of the government is to attain prosperity of people. The present study attempts to observe the effectiveness of poverty alleviation trends of Nepal on the basis of different plans. Furthermore, my findings emphasize on the effective measures of poverty alleviation. My argument is that Nepal needs to pay more attention for generating employment opportunities of the nation by increasing investment and modernization in agriculture.